Effects of Mindful Eating on the Mental Health of Students at State Universities in Malang - Mihmidati Hilmia; Umi Wasilatul Firdausiyah; Hasan Abdul Wafi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This research discusses the practice of mindful eating of female students at State Universities in Malang and whether it affects their mental health. This paper aims understand the relationship between mindful eating and mental health. The sample is taken from students of five state universities in the city of Malang. The methodology in this study is quantitative in terms of numerical data analysis and statistical processing, which is assisted by data collection techniques such as analytical surveys as a way of collecting data on a large enough population. Seventy-one percent (128 respondents) of the acquired data came from open and closed questionnaires. Many students did not understand the concept of mindful eating and its application. The choice of food type was determined based on the feelings or emotions. In addition, weak mindful eating was also found to be more common in respondents who did multitasking eating. The results of the study prove that few female students actually practice mindful eating process well. This shows that there is a lack of attention to mental health.Diskursus penelitian ini mengacu pada mindful eating mahasiswi di Perguruan Tinggi Negeri kota Malang yang berpengaruh pada kesehatan mental mereka. Tujuan dari tulisan ini tidak lain untuk memperoleh hasil reseacrh hubungan dari mindful eating dengan kesehatan mental, yang diambil dari sampel mahasiswi Perguruan Tinggi Negeri (PTN) Malang. Kemudian terkait metodologi pada penelitian ini bersifat kuantitatif pada ranah analisis data angka dan diolah secara statistik, yang dibantu dengan teknik pengumpulan data melalui survei analitik untuk mengumpulkan data pada populasi yang cukup besar. Data penelitian ini menemukan sebanyak 71% (128 responden) dari data kuesioner terbuka dan tertutup, bahwa para mahasiswinya banyak yang belum memahami konsep mindful eating beserta penerapannya, dimana pemilihan jenis pangan ditentukan berdasarkan perasaan atau emosi yang sedang dirasakan. Selain itu, lemahnya mindful eating juga ditemukan lebih banyak pada responden yang melakukan aktivitas makan secara multitasking (bersamaan dengan aktivitas lain). Hasil penelitian membuktikan bahwa sedikit mahasiswi yang benar-benar melakukan proses mindful eating dengan baik, dan hal ini membuktikan adanya ketidak sadaran dan kurangnya perhatian terhadap kesehan mental.